Ag@AgCl quantum dots embedded on Sn3O4 nanosheets towards synergistic 3D flower-like heterostructured microspheres for efficient visible-light photocatalysis. Issue 15 (15th October 2020) - Han, Yuqi; Wei, Miaomiao; Qu, Shuangyan; Zhong, Ming; Han, Lijuan; Yang, Haidong; Liu, Yang; Su, Bitao; Lei, Ziqiang
Abstract: Taking advantage of the oil-water interface, we introduced Ag@AgCl quantum dots (QDs) onto 2D Sn3 O4 nanosheets to fabricate a composite photocatalyst with a 3D flower-like structure (denoted as Ag@AgCl/Sn3 O4 ). Using the degradation of tetracycline hydrochloride (TC-HCl) and methylene blue (MB) as the examples, the as-prepared Ag@AgCl/Sn3 O4 composite with Ag@AgCl weight loading of 1% indicated 9.6 and 7.88 times higher photocatalytic activity than the Sn3 O4 nanosheets. Within both degradation reactions, hydroxyl radicals (OH) and superoxide radicals (O 2− ) were identified as the critical oxidation intermediates based on radical trapping and electron spin resonance (ESR) experiments. The unique morphology and photoelectrochemical properties of the as-prepared composites suggested the introduced Ag@AgCl QDs cooperated with the Sn3 O4 semiconductor to enhance the utilization of solar energy. Overall, the established heterojunction helped to reduce the transfer barrier of the photoinduced charge carriers, wherein the surface plasmonic resonance (SPR) of Ag nanoparticles was believed to take the main responsibility. The present work combines the Ag@AgCl-QDs and flower-like 3D Sn3 O4 microspheres for the first time to achieve an impressive degrading rate of TC-HCl and MB at the Ag@AgCl weight loading as low as 1%. Graphical abstract: The enhanced photocatalytic activity was attributed to the increased surface area, tight interface contact, surface plasmonic resonance (SPR) of Ag nanoparticles and the light scattering effect of the flower-like structure Sn3 O4 . Image 1 Highlights: Ag@AgCl QD-decorated flower-like Sn3 O4 photocatalysts were prepared. Ag@AgCl QDs increased visible-light absorption and the electron transfer effect of Sn3 O4 . The catalyst exhibited an enhanced photocatalytic degradation for TC-HCl and MB.